Status, Distribution, and Threats of Striped Hyena (Hyaena hyaena Linnaeus, 1758) in Nepal: A Review - Asmit Neupane; Asmita Regmi; Aastha Tiwari; Byanjana Sharma; Amit Adhikari; Bijaya Neupane (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
Striped hyena (Hyaena hyaena) is a member of the Hyaenidae family distributed globally from Africa to Central Tanzania, the Arabian Peninsula, Turkey, Central Asia, and the Indian subcontinent including Nepal. Only a few documented studies have been carried out at a national as well as international level regarding their habit, habitat, threats, and conservation measures. Various open access works of literature including articles, reports, and books published from 1941 to 2021 were assessed through Google scholar and Research gate for this study. We searched, refined, and selected 42 pieces of literature for the study purpose. We found that striped hyenas were recorded from five national parks of lowland Terai regions and they were recorded in six districts lying outside the protected area in Central and Western Terai as well as the hilly region of Nepal. Habitat degradation, decreased prey population, retaliatory killing by poisoning, poaching and road kills are found to be the major threats to these endangered scavengers that require immediate conservation initiatives We believe that this manuscript can fulfill the knowledge gap on this species and suggests conservation initiatives, which could be a landmark for conducting further research and conservation of striped hyenas.